EGRec: a MOOCs course recommendation model based on knowledge graphs - Yuefeng Cen; Shuai Jiang; Wenxuan Cai; Gang Cen (Discover Applied Sciences)
Abstract Massive open online courses (MOOCs) provide abundant learning resources but also overwhelm learners with their sheer volume, leading to challenges such as data sparsity and cold-start issues in conventional recommendation systems. To address these challenges, we propose EGRec, a novel course recommendation model that combines knowledge graphs and Heterogeneous Graph Attention Networks to improve recommendation precision, diversity, and relevance. By integrating multimodal data and explicitly leveraging dynamic subgraphs, EGRec captures intricate semantic relationships between courses and knowledge points, and dynamically adapts to learners’ evolving preferences. Extensive experiments on three real MOOCs datasets (ASSISTments 2009, ASSISTments 2015, and XueTangX) show that EGRec achieves up to 4%–5% improvements over state-of-the-art methods in HR@20, nDCG@20, and MRR. Our contributions include the design of a dynamic graph-enhanced model architecture, a novel multimodal fusion strategy, and substantial empirical gains in recommendation accuracy. These results highlight EGRec’s potential to enhance tailored learning experiences.